TEMPORARY PACING FOR SYMPTOMATIC BRADYCARDIA IN TRAUMATOLOGY INTENSIVE CARE UNIT - Janushevski F; Gavrilovska-Brzanov A; Jovanovski -Srceva, M; Stojanoski S; Georgiev, A (“Ss. Cyril and Methodius” University, Skopje, R.N.Macedonia, Department of Anaesthesia and Reanimation Faculty of Medicine, 2022)
Cardiac complications are not uncommon during surgical procedures. Not infrequently surgical medical problems are combined with cardiac conduction diseases with electrical disorder in the conduction system of the heart. The aim of this paper is to present a case report with such a combined condition and the need for setting of temporary pacemaker. We present a patient with a history of atrial fibrillation, arterial hypertension, chronic kidney disease and diabetes mellitus that was admitted at orthopedic department for femoral neck fracture. Patient had atrial fibrillation (AF) with complete AV block conduction, and heart rate around 40bpm, and with cardiologist consultations it was decided that the patient needed cardiac pacing at the time. At that time in patient a temporary endocardial pacing in intensive care unit was done. This report shows the importance of multidisciplinary approach and overall emphasizes the global knowledge for the need and the ways and different sites of cardinal pacing in complex cardiac diseases.
Keywords: complete AV block; temporary pacing; femoral neck fracture